Seismic Response and Safety Assessment of an Existing Concrete Chimney under Wind Load - Xuansheng Cheng; Hongjie Qian; Chao Wang; Xuedong Fu (Shock and Vibration)
A safety assessment of a chimney under the action of wind and earthquake is performed on one of the reinforced concrete chimneys in the Jinchuan company in China. The assessment is based on the linear filtering method, and wind loads of several heights on one field are simulated by MATLAB. The displacement of the structure under the action of wind load and earthquake is analyzed using maximum value superposition, and the stress on the chimney is calculated in four cases using the equal curvature criterion method. The time-history responses of the tall chimney structure under linear and nonlinear elastic conditions are discussed. The results show that for a chimney under wind load or frequent earthquakes, the displacement limit can meet the code requirements; however, under the combined action of frequent earthquakes and wind load, the structural displacement is bigger than other conditions. When the chimney is acted upon by a wind load, frequent earthquake action, or the combined action of wind load and frequent earthquake action, the maximum compressive stress, maximum tensile stress, and maximum shear stress are concentrated at the bottom of the chimney. The ultimate bearing capacity of a reinforced concrete chimney under three conditions can meet the original design requirements, but the maximum compressive stress at the bottom approaches the designed tensile limit value under the action of rare earthquakes; under these conditions, the bottom of the chimney may experience partial damage.